2020
DOI: 10.1002/hbm.24915
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala and nucleus accumbens involvement in appetitive extinction

Abstract: Extinction of appetitive conditioning is regarded as an important model for the treatment of psychiatric disorders like addiction. However, very few studies have investigated its neural correlates. Therefore, we investigated neural correlates of appetitive extinction in a large human sample including all genders (N = 76, 40 females) to replicate and extend results from a previous study. During differential appetitive conditioning, one stimulus (CS+) was paired with the chance to win a monetary reward, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Firstly, to be comparable with previous research on IU and uninstructed Pavlovian conditioned threat (Morriss et al, 2015, Morriss, Christakou, et al, 2016, Morriss, Macdonald, et al, 2016), the current study used an uninstructed Pavlovian conditioned reward (i.e., to receive the reward no action is required). However, as far as we are aware only one study to date has used monetary reward with an uninstructed Pavlovian design (Tapia Leon et al., 2018), and the majority of research has used uninstructed instrumental designs (Kruse et al., 2018, 2020; Kruse et al., 2017; i.e., to receive the reward an action needs to be made). Thus, the current study provides important information on Pavlovian conditioned reward generally and in relation to IU but there is limited research to directly compare against.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, to be comparable with previous research on IU and uninstructed Pavlovian conditioned threat (Morriss et al, 2015, Morriss, Christakou, et al, 2016, Morriss, Macdonald, et al, 2016), the current study used an uninstructed Pavlovian conditioned reward (i.e., to receive the reward no action is required). However, as far as we are aware only one study to date has used monetary reward with an uninstructed Pavlovian design (Tapia Leon et al., 2018), and the majority of research has used uninstructed instrumental designs (Kruse et al., 2018, 2020; Kruse et al., 2017; i.e., to receive the reward an action needs to be made). Thus, the current study provides important information on Pavlovian conditioned reward generally and in relation to IU but there is limited research to directly compare against.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that during reward acquisition training, skin conductance responding and liking ratings would be higher, and corrugator supercilii activity would be lower, to the learned reward (CS+) versus neutral (CS−) cues, indicative of conditioned responding (Andreatta & Pauli, 2015; Ebrahimi et al., 2019; Kruse et al., 2017; Kruse et al., 2018; Kruse et al., 2020; Tapia León et al., 2018; Tapia León et al., 2019; van den Akker et al., 2017; Wardle et al., 2018). Given the lack of IU‐related findings for the acquisition training phase in past research, we did not have any specific IU hypotheses for the acquisition training phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human neuroimaging studies have repeatedly identified activity within dopaminergic midbrain, VS (including NAcc), OFC, dorsal ACC, and amygdala during appetitive Pavlovian conditioning [120,[155][156][157][158][159][160][161][162]; for a meta-analysis, see 163]. In line with preclinical evidence showing that the infralimbic PFC promotes extinction recall, regulating Pavlovian relapse phenomena [141,164], the vmPFC is considered particularly relevant for the recall of extinction memory, in concert with striatum and amygdala [165][166][167][168], and the inhibition of appetitive responses [117,169].…”
Section: Behavioral Paradigms and Neural Circuitrymentioning
confidence: 96%
“…Human studies often employ differential conditioning protocols in which one stimulus (CS+) is paired with the US while a second (CS−) is not. Both appetitive and aversive CRs have been quantified on various response systems, including subjective ratings, psychophysiological measures, and neuroimaging [116][117][118][119][120]. Recent research has found evidence of behaviors similar to sign-and goal-tracking in healthy participants.…”
Section: Behavioral Paradigms and Neural Circuitrymentioning
confidence: 99%